2020
DOI: 10.4102/jsava.v91i0.2023
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of veterinary importance from domestic animals in uMkhanyakude district of KwaZulu-Natal province

Abstract: This study investigated the occurrence and phylogenetic relationship of protozoan parasites and Ehrlichia infecting domestic animals from three municipalities in uMkhanyakude district of KwaZulu-Natal province, South Africa. A total of 208 blood samples collected from clinically healthy cattle, sheep, goats and dogs from uMkhanyakude district were examined by polymerase chain reaction (PCR) assays, using either genus or species-specific primers to determine the occurrence and phylogenetic relationship of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Although serological methods seem to lack sensitivity and specificity, they remain a standard tool for the qualitative detection of antibodies [64]. Studies that used LAT [3,56,60], histology [28,33,34], and molecular techniques [48,50,92] were few, while others used the combination of one or two of LAT, MAT, ELISA, IFAT, DT, CF, Wolstenholme's modification, and Sabin-Feldman dye test techniques [30,32,35,41,42,54,59,93,94]. A recent study comparing three serological diagnostic tools showed that ELISA and IFAT had relatively higher sensitivity and specificity than MAT [95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serological methods seem to lack sensitivity and specificity, they remain a standard tool for the qualitative detection of antibodies [64]. Studies that used LAT [3,56,60], histology [28,33,34], and molecular techniques [48,50,92] were few, while others used the combination of one or two of LAT, MAT, ELISA, IFAT, DT, CF, Wolstenholme's modification, and Sabin-Feldman dye test techniques [30,32,35,41,42,54,59,93,94]. A recent study comparing three serological diagnostic tools showed that ELISA and IFAT had relatively higher sensitivity and specificity than MAT [95].…”
Section: Discussionmentioning
confidence: 99%
“…Forest plot of prevalence estimates of Toxoplasma gondii infections in Southern Africa. The confidence interval (CI) was 95%, and the diamond represents the pooled estimate (blue squares represent point estimation of the study weighted for population size)[3,5,19,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
mentioning
confidence: 99%
“…The lowest prevalences were observed in Southern Gauteng, Free State, and Western Cape, where the prevalences amounted to 4.4%, 5.4%, and 6.4%, respectively [ 41 ]. In another study, on 126 apparently healthy dogs from four welfare organizations and two townships in the greater Cape Town region (South Africa), B. rossi DNA was detected in 16 (12.7%) dogs, while in a separate study in Umkhanyakude District Municipality (KwaZulu-Natal province, South Africa), no B. rossi DNA was detected in 49 apparently healthy dogs [ 54 , 55 ]. It should also be noted that, in a retrospective study from the Onderstepoort Veterinary Academic Hospital (Faculty of Veterinary Science, University of Pretoria) in South Africa, 1222 out of 12,706 (9.6%) dogs had babesiosis during the period 2004–2010.…”
Section: Prevalence Of Babesia Rossimentioning
confidence: 99%
“…South Africa (7 out of 9 provinces) 36.9% (420 out of 1138) 2000-2006 [41] Cape Town region 12.7% (16 out of 126) Before 2014 1 [54] Eastern South Africa: KwaZulu-Natal province 0% (0 out of 49) Before 2020 1 [55] South Africa (Onderstepoort Veterinary Academic Hospital, University of Pretoria)…”
Section: South Africamentioning
confidence: 99%
“…al., 2009;Domingos et al, 2013;Tagwireyi et al, 2019), histology(Smit, 1961;Bigalke, et al, 1966;Du Plessis et al, 1967), and molecular techniques(Lukášová et al, 2018;Mofokeng et al, 2020;Rifkin et al, 2020) were few, while others used the combination of one or two of LAT, MAT, ELISA, IFAT, DT, CF, Wolstenholme's modification, and Sabin-Feldman dye test techniques(Fasser, et al., 1955; Hove et al, 2005b; Mc Connell et al, 1973; Zumla et al, 1991; Pandey, and Van Knapen 1992; Hove, T.; Dubey; Kistiah et al, 2011). A recent study comparing three serological diagnostic tools showed that ELISA and IFAT had relatively higher sensitivity and specificity than MAT (Sharma et al, 2019).…”
mentioning
confidence: 99%